Investigating Variability-aware Smells in SPLs: An Exploratory Study - Souza, Iuri Santos; Machado, Ivan; Seaman, Carolyn; Gomes, Gecynalda; Chavez, Christina; de Almeida, Eduardo Santana; Masiero, Paulo (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2019: Anais do XXXIII Simpósio Brasileiro de Engenharia de Software, 2019)
Variability-aware smell is a concept referring to artifact shortcomings in the context of highly-configurable systems that can degrade aspects such as program comprehension, maintainability, and evolvability. To the best of our knowledge, there is very little evidence that variability-aware smells exist in Software Product Lines (SPLs). This work presents an exploratory study that investigated (I) evidence that variability-aware smells exist in SPLs and (II) new types of variability-aware smell not yet documented in the literature based on a quantitative study with open source SPL projects. We collected quantitative data to generate reliable research evidence, by performing feature model and source code inspections on eleven open-source SPL projects. Our findings revealed that (1) instances of variability-aware smells exist in open-source SPL projects and (2) feature information presented significant associations with variability-aware smells. Furthermore, (3) the study presented six new types of variability-aware smells.